Fikih Reproduksi Perempuan: Tinjauan Terhadap Aborsi dan Pernikahan Dini - Rusli, Rusli (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2009)
This study aims to examine Islamic fiqh views on abortion and early marriage as issues in women's reproduction. Using a qualitative method with a normative-analytical approach, this study analyzes various opinions in classical and contemporary fiqh on abortion and early marriage. The results showed that in fiqh, abortion is generally considered haram, except in certain conditions that endanger the mother's life, while early marriage is viewed from various perspectives, depending on the social and cultural context. However, there is a consensus among scholars regarding the importance of protecting women's health and rights. This study concluded that women's reproductive fiqh needs to be understood in a modern context, with attention to aspects of health, women's rights, and the principle of justice in Islam.